Is there life on the airway tree? A pilot study of bronchial cell vitality and tissue morphology in the ex vivo lung perfusion (EVLP) era of lung transplantation. Issue 11 (28th June 2022) - Boffini, Massimo; Cassoni, Paola; Gambella, Alessandro; Simonato, Erika; Delsedime, Luisa; Marro, Matteo; Fanelli, Vito; Costamagna, Andrea; Lausi, Paolo Olivo; Solidoro, Paolo; Scalini, Fabrizio; Barbero, Cristina; et al.
Abstract: Background: Ex vivo lung perfusion (EVLP) is a relevant procedure to increase the lung donor pool but could potentially increase the airway tree ischemic injury risk. Methods: This study aimed to evaluate the direct effect of EVLP on the airway tree by evaluating bronchial cell vitality and tissue signs of injury on a series of 117 bronchial rings collected from 40 conventional and 19 EVLP‐treated lung grafts. Bronchial rings and related scraped bronchial epithelial cells were collected before the EVLP procedure and surgical anastomosis. Results: The preimplantation interval was significantly increased in the EVLP graft group ( p < 0.01). Conventional grafts presented cell viability percentages of 47.07 ± 23.41 and 49.65 ± 21.25 in the first and second grafts which did not differ significantly from the EVLP group (first graft 50.54 ± 25.83 and second graft 50.22 ± 20.90 cell viability percentage). No significant differences in terms of histopathological features (edema, inflammatory infiltrate, and mucosa ulceration) were observed comparing conventional and EVLP samples. A comparison of bronchial cell viability and histopathology of EVLP samples retrieved at different time intervals revealed no significant differences. Accordingly, major bronchial complications after lung transplant were not observed in both groups. Conclusions: Based on these data, we observed that EVLP did not significantly impact bronchial cell vitality and airway tissue preservation nor interfere with bronchial anastomosis healing, further supporting it as a safe and useful procedure. Abstract : Graphical representation of the study design, procedures, and results. Cases were retrieved to represent conventional and EVLP grafts.